Jalāl al-Dīn al-Rūmī’s concept of Ibtilā’: its application to stress management - Bahari, Che Amnah; Faris, Waleed Fekri Faris; Mohamad, Mardiana (IIUM Press, 2021)
Spiritual handling in stressful situation plays a vital role in revitalizing the affected persons. Since the beginning, counselling and psychotherapy's main approaches have been overlooking religion and spirituality as factors that influence the human psyche. The contemporary counselling approaches focus on changes in emotional, cognitive, and behavioural aspects of their clients. Spirituality and religiosity were considered unscientific components which cannot be measured objectively. Yet, due to the failure of some contemporary approaches in handling overly complex problems of human beings or ibtilā‟ in these modern days, there has been an increasing interest in the role of spirituality and religion in psychotherapy. Historically, the great Muslim scholar Jalāl al-Dīn al-Rūmī in his Mathnawī has provided numerous couplets towards the healing process. This paper aims to explore al-Rūmī‟s concepts of al-ibtilā.‟ and its relevancy in stress management. It also discusses his thought mentioned in his poems, stories, Qur‟ānic citation and religious observance in life. The applicability and advantages of al-Rūmī‟s philosophy to an individual's management of stress in modern life are highlighted in this paper.